EUV Beam–Foil Spectra of Germanium and a Blind-Spot Problem in Spectroscopy - Elmar Träbert (Atoms, 2023)
Beam–foil extreme-ultraviolet survey spectra of Ge (<semantics>Z=32</semantics>) are presented. The data have been garnered at the performance limit of the heavy-ion accelerator available, with a correspondingly limited statistical and calibrational reliability. However, the Ge spectra have been recorded at various delays after excitation, and this technique points to a possible blind spot in some other spectroscopic techniques, and thus in the literature coverage. A similarly patchy coverage can be noted in various atomic structure computations. The experimental and theoretical gaps seem to be correlated.